PERSEPSI KEMUDAHAN DAN KEMANFAATAN SISTEM INFORMASI MANAJEMEN PUSKESMAS (APLIKASI SISTEM PENDAFTARAN DAN PELAPORAN) DI PUSKESMAS DANUREJAN II KOTA YOGYAKARTA - , RAKHMAN DWI SAMPURNA, Arief Kurniawan, SKM. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Nowadays the development of science and technology demands to advance the field of information, because the information affects the progress of the work of an organization in servicing community needs of goods and services. In health services, information systems data which are suitable for the need of health services support in providing the effective and accurate services to the public. Primary health-care (Saryankes) facilities play a vital role as it becomes the first referral of patients. One of the primary care facilities that have implemented health center information system is Danurejan II. Nobody has conducted an evaluation of dairy ease and expediency in that health center. In that health care center, researchers are interested in knowing perception of the ease and usefulness of SIMPUS. Objective: Knowing the user's perception SIMPUS on registration and reporting system application related aspects of convenience and expediency in health centers SIMPUS Danurejan II. Method: The method in this research is descriptive qualitative approach. Researcher chose all SIMPUS users as the subject of his study, while the object is the information systems used in health centers health centers Danurejan II. Researcher collected data through observation and interviews techniques. Results: Four of five respondents said that it was easy to use SIMPUS because it fulfilled the indicators that is proposed by Davis (1989), that is easy to learn, easy data retrieval, flexible in the search for the data collection, easy to operate, the display is clear and understandable, but one of the five respondents stated that SIMPUS had not easy yet to use because exploring data on the reporting LB2 (LPLPO) cannot be done well. Four of five respondents in the health center using SIMPUS in Danurejan II stated that SIMPUS provided benefits, but one of five respondents stated that SIMPUS had not given the benefit of reporting of LB2 because the database has not been updated so that the SIMPUS users cannot use the SIMPUS in making a LB2 (LPLPO) report. The functions of registration application according to Abdelhak theory (2007), in Budiâs research (2013), SIMPUS have deficiencies in the term of the registration application because it can only display the ID card on the overview of patient data and cannot display the overall patientâs guarantees. The reporting application function of SIMPUS has shortcomings because it has not been able to update the database list of drugs, that are the basis of data in making a report, so in making an LB2 (LPLPO) report does not use SIMPUS but uses manual process.